A Threshold Concept and Capability Approach to the Cross-Cultural Contextualization of Western Management Education. (February 2020) - Lamb, Peter; Hsu, Shih-Wei; Lemanski, Michal
This article presents contextualization as a pedagogic response to the issues of cross-cultural relevance associated with Western management education in non-Western contexts, and with regard to the needs and expectations of non-Western students. Building on a synthesis of threshold concepts and threshold capabilities, this article demonstrates in principle how contextualization is a threshold concept that can help educators and students address the issue of relevance. Translation intelligence is introduced as a distinct threshold capability, which can enable the development of the knowledge handling skills necessary for students' future management practice. This article posits that contextualization and translation intelligence are valuable to business schools and management educators because they address issues of cross-cultural relevance and by facilitating learning beyond content they equip students with skills which can be employed in their future management practice.